2008
DOI: 10.1103/physrevb.77.024430
|View full text |Cite
|
Sign up to set email alerts
|

Changeover from glassy ferromagnetism of the orbital domain state to long-range ferromagnetic ordering inLa0.9Sr0.1MnO3

Abstract: An attempt is made to resolve the controversy related to the low temperature phase (ground state) of the low-doped ferromagnetic (FM)-insulator(I) manganite through bulk magnetic measurements on La0.9Sr0.1MnO3 sample. It is shown that the FM phase, formed out of well defined transition in the low-doped system, becomes inhomogeneous with decrease in temperature. This inhomogeniety is considered to be an outcome of the formation of orbital domain state of eg-electrons having hole rich (metallic) walls separating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
1
20
0
Order By: Relevance
“…In the samples heat treated at 900 and 1100 C, a second peak is observed in  curves in agreement with the change of  falling rate around the same temperature area. Similar behavior is also seen in La 0.8 Pb 0.2 MnO 3[3], La 0.46 Sr 0.54 Mn 1-y Cr y O 3[14], La 0.9 Sr 0.1 Mn 1-y Ga y O 3[15], La 0.85 Ca 0.15 Mn 0.95 Fe 0.05 O 3[6], and La 0.9 Sr 0.1 MnO 3[16] perovskites. There are various possible reasons about this behavior.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…In the samples heat treated at 900 and 1100 C, a second peak is observed in  curves in agreement with the change of  falling rate around the same temperature area. Similar behavior is also seen in La 0.8 Pb 0.2 MnO 3[3], La 0.46 Sr 0.54 Mn 1-y Cr y O 3[14], La 0.9 Sr 0.1 Mn 1-y Ga y O 3[15], La 0.85 Ca 0.15 Mn 0.95 Fe 0.05 O 3[6], and La 0.9 Sr 0.1 MnO 3[16] perovskites. There are various possible reasons about this behavior.…”
supporting
confidence: 79%
“…6) of the milled powder heat treatment at 1200 C for 1 h, confirms the stoichiometric composition of La 0.8 Ba 0.2 MnO 3 . Mukherjee et al [16] showed in La 0.9 Sr 0.1 MnO 3 . However, this reason may not be possible because of the frequency dependent of  peaks for these kinds of perovskites [3].…”
Section: Figmentioning
confidence: 98%
“…The different techniques gave complementary information but their conclusions did not always point to the same direction maintaining some uncertainty in several fundamental aspects. The presence of different kinds of electronic 3 and/or chemical inhomogeneities, 4 glassy behavior, 2 Griffiths phase, 5 or nanophase segregation 6 in the different temperature ranges have been invoked to explain the observations. But also homogeneous pictures of the low-temperature phases have been reported.…”
Section: Introductionmentioning
confidence: 96%
“…Since the magnetic transition at ϳ175 K is likely associated with a structural transition which occurs at the same temperature, 9 it would be logical to infer that the structural transition may lead to a variation in the size and distribution of clusters and hence the spin dynamics in the sample. 15 However, further study of this structural transition needs to be done to further elucidate any relationship between it and the relaxation dynamics observed in the ac magnetic response. The important fact that clearly emerges for the first time from our study is that the LuFe 2 O 4 system undergoes a phase transition from a paramagnetic phase to a ferrimagnetic phase at ϳ240 K followed by a re-entrant cluster glass transition below 225 K with an additional magnetic transition that exhibits cluster glass characteristics, also being present around 170 K. We note again that while the peak in ZFC magnetization at 225 K was interpreted in the past as due to an antiferromagnetic transition, 7,8 our data and experiments from another group 10 have now clarified this to be a result of 3D ferrimagnetic ordering followed by a re-entrant glass transition.…”
mentioning
confidence: 99%